Neurologic Phenotypes Associated with Mutations in TREX1, RNASEH2A, RNASEH2B, RNASEH2C, SAMHD1, ADAR1, and IFIH1: Aicardi–Goutières Syndrome and Beyond - Livingston, John H.; Crow, Yanick J. (Neuropediatrics, 2016)
The Aicardi–Goutières syndrome (AGS) was first described in 1984, and over the following years was defined by the clinical and radiological features of an early onset, severe, neurologic disorder with intracranial calcification, leukoencephalopathy, and cerebral atrophy, usually associated with a cerebrospinal fluid (CSF) pleocytosis and elevated CSF interferon α activity. It is now recognized that mutations in any of the following seven genes may result in the classical AGS phenotype: TREX1 (AGS1), RNASEH2A (AGS2), RNASEH2B (AGS3), RNASEH2C (AGS4), SAMHD1 (AGS5), ADAR1 (AGS6), and IFIH1 (AGS7). All of these genes encode proteins involved in nucleotide metabolism and/or sensing. Mutations in these genes result in the induction of type 1 interferon production and an upregulation of interferon stimulated genes. As more patients harboring mutations in these genes have been described, in particular facilitated by the advent of whole exome sequencing, a remarkably broad spectrum of associated neurologic phenotypes has been revealed, which we summarize here. We propose that the term AGS has continued clinical utility in the designation of a characteristic phenotype, which suggests relevant diagnostic investigations and can inform outcome predictions. However, we also suggest that the use of the term “type 1 interferonopathy” is appropriate for the wider spectrum of disease consequent upon dysfunction of these genes and proteins since it implies the possibility of a common “anti-interferon” approach to therapy as such treatments become available.
Keywords: Aicardi–Goutières syndrome; type 1 interferonopathies; interferon signature